Effect Measure Modification of Multimorbidity On the Association Between Regularity of General Practitioner Contact and Potentially Avoidable Hospitalisations - Moorin, Rachael (International Journal of Population Data Science, 2020)
Introduction Regular contact with a general practitioner (GP) has been shown to lower the risk of potentially avoidable hospitalisations (PAHs) independently of continuity of provider and frequency of contact. Multimorbidity affects between 55 and 98% people aged 65+ years and continues to place pressure on healthcare systems globally. However, little is known about its impact on the relationship between continuity of primary care and PAHs. Objectives and Approach A retrospective, longitudinal cohort study using survey data linked to routinely-collected administrative health data from the 45 and Up Study conducted in New South Wales, Australia was used to investigate the effect measure modification by multimorbidity on the relationship between regularity of GP contact and PAHs. Multimorbidity was assessed using the Rx-Risk comorbidity score, which captures the number of condition groups, assigned based on medicine dispensing records, using a 5-year look-back period. PAHs were: (i) any unplanned hospitalisations, (ii) chronic ambulatory care sensitive conditions (ACSC) hospitalisations or (iii) unplanned ACSC hospitalisations. Multivariable logistic regression and population attributable fractions (PAF) were used to examine effect measure modification by multimorbidity. Results Higher GP regularity was significantly associated with a reduction in the probability of each PAH type. This reduction diminished with increasing multimorbidity with the effect measure modification most apparent for chronic ACSC and unplanned chronic ACSC hospitalisations. The PAF of moving to the highest quintile of regularity significantly reduced with increasing multimorbidity. For example, a reduction in the PAF of unplanned ACSC hospitalisations of 31.1% was observed in those with a RX Risk score of >10 (17.8%) compared with those with no multimorbidity (48.9%). Conclusion / Implications Weakening of the relationship between GP visit regularity and PAHs with increasing levels of multimorbidity suggests a need to focus on improving primary care support to prevent PAHs for patients with multimorbidity.